EUTHANASIA DALAM PERSPEKTIF HUKUM POSITIF DAN POLITIK HUKUM PIDANA DI INDONESIA - Khoiruddin Manahan Siregar; Syafruddin Kalo; Muhammad Hamdan; Edi Yunara (Universitas Sumatera Utara, 2018)
ABSTRACT Euthanasia is an attempt to end someone life when he/she has an uncurable illness, euthanasia will be done in order to release his/her from suffering his/her illness. In Indonesia, euthanasia can not be done and it is classified as an illegal act. Both in the positive law and the ethics code regulate that performing an euthanasia is not allowed. The type of research conducted in this study is normative legal research, normative legal research is a method of research that refers to the norms, theories, principles, and rules contained in various positive laws so that it refers to the legal or commonly called criminal law politics. The results of this thesis writing study can be concluded that euthanasia if viewed from the aspects of positive law and political criminal law in Indonesia is still experiencing debate that has not found the end, because between the granting of human rights with the contradictions of national law, especially the Criminal Code applied in Indonesia, but basically that the act of euthanasia is still an act that is prohibited in the criminal law system or health law that exist in Indonesia, regardless of the reasons and the reasons used and whoever proposes both the person who wants to be his or her own family is still prohibited from committing the act of euthanasia, even health workers as well it is still prohibited to perform such euthanasia for any reason. Keywords: Euthanasia, Positive Law, Medical Ethics, Political Criminal Law